Answer:
m = -3
Step-by-step explanation:
5m + 20 = 8 + 2m +3
5m + 20 = 11 +2m
3m + 20 = 11
3m = -9
m = -3
Answer:
yes
Step-by-step explanation:
Answer:
x = 5/-6 + (√13)/-6
x = 5/-6 -(√13)/-6
Step-by-step explanation:
2x^2 = -x^2 - 5x - 1. Subtract 2x^2 from both sides.
-3x^2 - 5x - 1. Do the quadratic formula.
That gives you:
-5/6 ± (√13)/-6.
3 triangles.
If you take 3 toothpicks you create the first triangle. You put the last toothpick down the middle, you get 2 more
Answer:
Step-by-step explanation:
The square root of 36 is 6!
Hope it helps